Career Adaptability of Trauma Survivors: The Moderating Role of Posttraumatic Growth. Issue 2 (8th June 2018) - Prescod, Diandra J.; Zeligman, Melissa
Abstract : Impaired functioning in occupational domains is a diagnostic characteristic of posttraumatic stress disorder, and yet the interactions between trauma and career remain understudied. This study examined the relationships between trauma symptoms, posttraumatic growth, and career adaptability in college students who identified as trauma survivors ( N = 215). Results indicated that (a) trauma symptoms and posttraumatic growth were both significantly predictive of career adaptability and (b) posttraumatic growth moderated the relationship between trauma and career adaptability. The impact of demographic factors and implications for career counselors and counselor educators are also discussed.